India in the new millennium - Alexander, P C (Mumbai Somiya, 2001)
India entered the twenty first century with a food surplus, self-sufficiency in production of consumer goods.The author is dealing with variety of important subjects,as important as the new millennium.These include democratic evolution economic policies,e
Keywords: India-Politics and government; Democracy-India